The Effect of Health Promotion Media on Knowledge of Work Safety and Health of Students of 3 State Vocational School, Jambi City - Andy Amir; Richard Aprialdy Sipahutar; Oka Lesmana S; Fitria Eka Putri; Hubaybah Hubaybah (Lembaga Pengembangan Kinerja Dosen, 2023)
Media or visual aids in health promotion can be interpreted as tools for promoting health that can be seen, touched, heard, tasted or smelled, to facilitate communication and dissemination of health information. The purpose of this study was to find out how the influence of the application of health promotion media (audiovisual) on increasing the knowledge of students at SMK Negeri 3 Jambi City. This study used the Pre-Experimental method by designing one group pretest and posttest. The research location was carried out at SMK Negeri 3 Jambi City. The study population consisted of 221 students and the sample was taken using a proportional stratified random sampling technique with a total of 65. Data analysis used the Paired/Related T test. The results of the study showed that there was an influence from the health promotion media intervention carried out on the knowledge of students at SMK Negeri 3 Jambi City. From the paired t-test conducted, the p-value for knowledge was 0.000. This proves that there is influence before and after being given an intervention using health promotion media. From this study it can be concluded that there is an influence of interventions using health promotion media on students' knowledge of occupational safety and health (K3) at SMK Negeri 3 Jambi City.